1997
DOI: 10.1073/pnas.94.20.10879
|View full text |Cite
|
Sign up to set email alerts
|

Role of tyrosine phosphorylation of a cellular protein in adeno-associated virus 2-mediated transgene expression

Abstract: The adeno-associated virus 2 (AAV), a single-stranded DNA-containing, nonpathogenic human parvovirus, has gained attention as a potentially useful vector for human gene therapy. However, the single-stranded nature of the viral genome significantly impacts upon the transduction efficiency, because the second-strand viral DNA synthesis is the rate-limiting step. We hypothesized that a host-cell protein interacts with the single-stranded D sequence within the inverted terminal repeat structure of the AAV genome a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

14
157
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 120 publications
(171 citation statements)
references
References 35 publications
14
157
0
Order By: Relevance
“…Regardless of the mechanism involved, the extent of viral second-strand DNA synthesis was consistent with the observed transcriptional activity of the vector genomes. [4][5][6][7][8][9][10][11] These data strongly argue that rather than strand-annealing, TC-PTP-mediated tyrosine dephosphorylation of FKBP52, or the absence of FKBP52, leads to efficient AAV second-strand DNA synthesis resulting in an increase in AAV-mediated transgene expression in hepatocytes in vivo. Although our data might appear at odds with the model proposed by Nakai et al, 2 which favors DNA strand-annealing as the mechanism of hepatocyte transduction, the simplest explanation is that viral secondstrand DNA synthesis is the rate-limiting step in B95% of hepatocytes, whereas DNA strand-annealing might be operative in B5% of hepatocytes.…”
Section: Aav-mediated Transduction Of Hepatocytesmentioning
confidence: 99%
See 3 more Smart Citations
“…Regardless of the mechanism involved, the extent of viral second-strand DNA synthesis was consistent with the observed transcriptional activity of the vector genomes. [4][5][6][7][8][9][10][11] These data strongly argue that rather than strand-annealing, TC-PTP-mediated tyrosine dephosphorylation of FKBP52, or the absence of FKBP52, leads to efficient AAV second-strand DNA synthesis resulting in an increase in AAV-mediated transgene expression in hepatocytes in vivo. Although our data might appear at odds with the model proposed by Nakai et al, 2 which favors DNA strand-annealing as the mechanism of hepatocyte transduction, the simplest explanation is that viral secondstrand DNA synthesis is the rate-limiting step in B95% of hepatocytes, whereas DNA strand-annealing might be operative in B5% of hepatocytes.…”
Section: Aav-mediated Transduction Of Hepatocytesmentioning
confidence: 99%
“…2,3 Others and we, on the other hand, have suggested that viral second-strand DNA synthesis is the rate-limiting step in AAV-mediated transgene expression. [4][5][6][7][8][9][10][11] We previously observed that following intravenous (i.v.) administration into the tail-vein, AAV vectors selectively target the liver in mice, but less than 5% of hepatocytes express the transgene.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…3,4 Thus, failure to undergo viral second-strand synthesis remains a predominant rate-limiting step in the observed low efficiency of singlestranded AAV (ssAAV) vector-mediated transgene expression both in vitro and in vivo. [5][6][7][8][9][10][11][12][13][14] The use of selfcomplementary AAV (scAAV) vectors that bypass the requirement for viral second-strand DNA synthesis can circumvent this problem. 13 However, their widespread use is limited by their limited packaging capacity (B3.3 kb), 15 which is significantly less than that of conventional ssAAV vectors (B6 kb).…”
mentioning
confidence: 99%